2003
DOI: 10.1038/sj.onc.1206526
|View full text |Cite
|
Sign up to set email alerts
|

MafA has strong cell transforming ability but is a weak transactivator

Abstract: The maf oncogene of the avian oncogenic retrovirus AS42 encodes a nuclear bZip protein, v-Maf, that recognizes sequences related to the AP-1 target site. The corresponding cellular protein, c-Maf belongs to a family of related bZip proteins together with MafA and MafB. In this paper, we compare the transactivation and cell transforming abilities of MafA and MafB along with two forms of the c-Maf protein. These proteins induce cellular transformation when expressed in chicken embryo fibroblasts. In reporter ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 38 publications
4
45
1
Order By: Relevance
“…This hypothesis is consistent with the human mutation reports; 5 of the 6 mutations of NRL, so far reported in patients with autosomal dominant retinitis pigmentosa, are at residues Ser-50 and Pro-51 (27)(28)(29), and the S50T mutation was shown to enhance the ability of NRL to transactivate the rhodopsin promoter in the presence of CRX (27). In addition, the identification of phosphorylation and subsequent mutation analysis of residue Ser-65 in MafA, the homologous residue of Ser-50 in NRL, further supports this hypothesis (58,59). To investigate it further, we altered individual serine and threonine residues (Ser-38, Ser-41, Thr-42, Ser-45, Ser-46, Ser-50, Thr-52, and Ser-54) to alanine and examined their effect on the transactivation ability of NRL using the rhodopsin promoter activity assay similar to that reported earlier (27).…”
Section: Discussionsupporting
confidence: 50%
“…This hypothesis is consistent with the human mutation reports; 5 of the 6 mutations of NRL, so far reported in patients with autosomal dominant retinitis pigmentosa, are at residues Ser-50 and Pro-51 (27)(28)(29), and the S50T mutation was shown to enhance the ability of NRL to transactivate the rhodopsin promoter in the presence of CRX (27). In addition, the identification of phosphorylation and subsequent mutation analysis of residue Ser-65 in MafA, the homologous residue of Ser-50 in NRL, further supports this hypothesis (58,59). To investigate it further, we altered individual serine and threonine residues (Ser-38, Ser-41, Thr-42, Ser-45, Ser-46, Ser-50, Thr-52, and Ser-54) to alanine and examined their effect on the transactivation ability of NRL using the rhodopsin promoter activity assay similar to that reported earlier (27).…”
Section: Discussionsupporting
confidence: 50%
“…Maf family members have been reported to act as both transcriptional activators or repressors and their characterized phosphorylation sites can serve to either stimulate or inhibit function (Nishizawa et al, 2003,Ochi et al, 2003. To determine if the c-Maf point mutants (S15A, S70A, and S15A/S70A) display cell type-dependent functional variability, we assessed their transactivation capacity in endothelial and liver epithelial cell lines (153/luc, Fig.…”
Section: Putative Phosphorylation Sites Of C-maf Are Differentially Umentioning
confidence: 99%
“…Although their oncogenic role appears to depend on cell type and tissue (Pouponnot et al, 2006;Rocques et al, 2007), several reports including their translocation in human multiple myeloma (Chesi et al, 1998) have firmly established the large Maf family members, MafA, MafB and c-Maf, as bona fide protooncogenes (Eyche`ne et al, 2008). It was shown that Maf proteins can transform primary cells (Nishizawa et al, 2003;Pouponnot et al, 2006). Their oncogenic activity was also demonstrated in multiple myeloma cell lines (Hurt et al, 2004) and in mice (Morito et al, 2006(Morito et al, , 2011.…”
mentioning
confidence: 99%